The relationship between the incidence of COVID-19 with the underlying diseases in hospitalized patients - Rasoul Raesi; Zahra Abbasi; Mehdi Raei; Kiavash Hushmandi (فصلنامه ابن سینا)
Background and aims: Covid-19 have more risks among patinets with underlying diseases. This study was performed to investigate the relationship between the incidence of Covid-19 and underlying diseases in hospitalized patients in Khaf city. Methods: This cross-sectional study was conducted from March 2020 to the end of August 2020 by examining the hospital records of 210 patients with Covid-19 from the corona ward and 105 non-Covid-19 patients from the orthopedic ward who were selected by available sampling method. Data related to demographic information and underlying disease was extracted from the patients' records. Data were analyzed by statistical tests of chi-square and logistic regression. Results: There was a significant difference in the frequency distribution of underlying diseases in in the two groups of patients with Covid-19 and without Covid-19 (p<0.001). The relative frequency of diabetes, hypertension, and kidney as well as heart diseases in patients with Covid-19 was significantly higher than that in patients without Covid19 (p<0.01). Conclusion: In this study, people with underlying disease had a higher chance of developing Covid-19. Therefore, health policy makers should provide programs for appropriate education, support, and awareness of patients with underlying diseases.